Market-driven security-constrained transmission network expansion planning - Garcés, Lina P. [UNESP]; Romero, Rubén [UNESP]; Lopez-Lezama, Jesús María (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper presents a Bi-level Programming (BP) approach to solve the Transmission Network Expansion Planning (TNEP) problem. The proposed model is envisaged under a market environment and considers security constraints. The upper-level of the BP problem corresponds to the transmission planner which procures the minimization of the total investment and load shedding cost. This upper-level problem is constrained by a single lower-level optimization problem which models a market clearing mechanism that includes security constraints. Results on the Garver's 6-bus and IEEE 24-bus RTS test systems are presented and discussed. Finally, some conclusions are drawn. © 2011 IEEE.
Keywords: Bi-level programming; electricity market; security constraints; transmission network expansion planning; Load-shedding; Market clearing mechanisms; Market environment; Optimization problems; Security constraint; Test systems; Total investment; Commerce; Constrained optimization; Electric power transmission networks; Expansion; Investments; Planning; Network security